Properties of Mortar Incorporating Spent Garnet as Fine Aggregates Replacement - Abdul Shukor Lim, Nor Hasanah; Alladin, Noor Fazura Najihah; Mohammadhosseini, Hossein; Ariffin, Nur Farhayu; Mazlan, Ain Naadia (International Journal of Integrated Engineering, 2020)
The rapid growth in the construction industry has increase in the consumption of fine aggregates whereby it depletes the natural resources. Also, garnet is a materials that can be reused for several times in the ship cleaning process. However, when this garnet can no longer be used, it is then are disposed in landfill, oceans and rivers, thus increase the volume of landfill waste and causing environmental problems. Therefore this research is aimed to study the effect of spent garnet as a fine aggregates replacement in terms of physical, fresh and hardened properties of mortar. In this study, several specimens are prepared by using different percentage of spent garnet range from 0%, 25%, 50%, 75% and 100% as a fine aggregates replacement in mortar. The specimens are casted using 50 mm x 50 mm x 50 mm mould and the materials used in preparing the mortar sample are cement, fine aggregates, water and spent garnet. The samples is then cured in the water before it is tested at the age of 7, 14, and 28 days. The characteristic of the materials and fresh and hardened properties of mortar were investigated. It was found that the workability of mortar increases with the increasing amount of spent garnet. Overall, it is found out that the spent garnet can be used as fine aggregates replacement in mortar up to 50% since it has a comparable strength (40 MPa at 28 days) with a conventional mortar with 16% improvement in water absorption test. In addition, the environmental impact can also be reduced through the use of spent abrasive waste by preserving the use of natural resources.